1996
DOI: 10.1146/annurev.ph.58.030196.003025
|View full text |Cite
|
Sign up to set email alerts
|

Post-Exercise Lactate Metabolism: A Comparative Review of Sites, Pathways, and Regulation

Abstract: Most vertebrates utilize supplemental lactate production to support the energetic demands of vigorous, brief exercise. Despite similar patterns of accumulation, there appears to be a trichotomy with regards to lactate processing post-exercise. Most fish retain most of their lactate intramuscularly, using it for in situ glycogen replenishment. Recent evaluation of fish muscle concludes that pyruvate kinase reversal is a probable gluconeogenic pathway. Amphibians and reptiles also utilize lactate as a muscle gly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
85
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(88 citation statements)
references
References 48 publications
2
85
1
Order By: Relevance
“…Muscle fructose 1,6-bisphosphatase (FBPase; EC 3.1.3.11) -a key enzyme of glycogen synthesis from non-carbohydrates [1][2][3] -for a long time was regarded to be soluble and freely diffused in the cytoplasm. However, our recent investigation revealed that, in striated muscles of mammals, FBPase colocalizes with sarcomeric a-actinin [4,5] and in cardiomyocytes and smooth muscle cells it is also present inside the cells' nuclei [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Muscle fructose 1,6-bisphosphatase (FBPase; EC 3.1.3.11) -a key enzyme of glycogen synthesis from non-carbohydrates [1][2][3] -for a long time was regarded to be soluble and freely diffused in the cytoplasm. However, our recent investigation revealed that, in striated muscles of mammals, FBPase colocalizes with sarcomeric a-actinin [4,5] and in cardiomyocytes and smooth muscle cells it is also present inside the cells' nuclei [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Our findings in terms of the fate of lactate are in keeping with those reported in toads (Withers et al, 1988) and lizards (Gleeson and Delassio, 1989) that the majority of lactate produced following activity is stored as glycogen, with <20% of lactate being oxidized. This 'carbon-recycling' pattern post-exercise is now well established for most ectothermic vertebrates (for reviews, see Gleeson, 1991;Gleeson, 1996). Based on label incorporation, both muscle and liver demonstrated glyconeogenic and gluconeogenic capacity (Fig.·6).…”
Section: The Post-activity Fate Of Lactate: Summermentioning
confidence: 73%
“…Fig.·3B clearly shows a lactate clearance pattern in which blood lactate levels remain significantly elevated for the entire course of recovery, despite the complete clearance of excess lactate from the skeletal muscle tissue (Fig.·4A). In contrast to these findings, blood and tissue lactate levels reported by Fournier et al (Fournier et al, 1994) in Rana pipiens demonstrate what could be considered to be a pattern of lactate clearance typically found in reptiles and mammals, in which extracellular levels remain equal to or lower than intracellular levels for the duration of recovery (for reviews, see Gleeson, 1991;Gleeson, 1996). Similar to our findings in bullfrogs, a lactate 'reversedgradient' following exercise recovery was observed in Rana temporaria, but only at hibernating temperatures (>7°C) in frogs submerged for several months (Tattersall and Boutilier, 1999).…”
Section: Characterization Of Metabolic Recovery From Activity: Summermentioning
confidence: 78%
“…Since blood lactate directly infl uences ExcessCO 2 [Yunoki et al, (2000)], the characteristics of muscle fi ber relative to lactic acid production and oxidation would affect ExcessCO 2 . It has been shown that Type II fi ber with high in contractile rate and anaerobic capacity relates to lactic acid production, whereas Type I fi ber with low in contractile rate and high in aerobic capacity relates to lactic acid oxidation [Gleeson, (1996)]. Therefore, we hypothesized that ExcessCO 2 could closely relate to both Type I and Type II fi ber.…”
Section: Discussionmentioning
confidence: 94%